2019
DOI: 10.3389/fpsyg.2019.01574
|View full text |Cite
|
Sign up to set email alerts
|

High-Tech and Tactile: Cognitive Enrichment for Zoo-Housed Gorillas

Abstract: The field of environmental enrichment for zoo animals, particularly great apes, has been revived by technological advancements such as touchscreen interfaces and motion sensors. However, direct animal-computer interaction (ACI) is impractical or undesirable for many zoos. We developed a modular cuboid puzzle maze for the troop of six Western lowland gorillas ( Gorilla gorilla gorilla ) at Bristol Zoo Gardens, United Kingdom. The gorillas could use their fingers or tools to interact with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 72 publications
1
35
0
Order By: Relevance
“…However, presence or use of the device did not affect time spent engaged in the majority of behaviors of the individuals studied. This reflects work by Perdue et al (2012) and Clark et al (2019) who similarly found no negative or positive effects of such enrichment strategies. There was a trend towards an increased time spent engaged in all play behavior in Dewi and Kiani who were also the two individuals in the study with the highest number of bouts of interactions with the device and the highest number of bouts of prolonged interaction.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…However, presence or use of the device did not affect time spent engaged in the majority of behaviors of the individuals studied. This reflects work by Perdue et al (2012) and Clark et al (2019) who similarly found no negative or positive effects of such enrichment strategies. There was a trend towards an increased time spent engaged in all play behavior in Dewi and Kiani who were also the two individuals in the study with the highest number of bouts of interactions with the device and the highest number of bouts of prolonged interaction.…”
Section: Discussionsupporting
confidence: 76%
“…A further point of difference for this enrichment design has been the lack of food reinforcement associated with use of the device, as employed in prior similar studies with orangutans (e.g., Perdue et al 2012). In the current study, engagement with the digital enrichment (with a few exceptions) was typically ad‐hoc and intermittent; rather than a focused activity as evidenced by the few interactions with the wall‐based system that lasted more than 10 s. While food‐based cognitive challenges such as puzzle feeders can engage orangutans in focused tasks for several minutes at a time, as Clark et al (2019) note, “there has never been a duration or proportion of time proposed as an ‘acceptable’ level of enrichment use” (p. 10–11). More general observations of orangutan behavior when engaging in foraging and non‐digital play highlight how orangutan interactions with most sources of enrichment, (such as forage, objects, and other orangutans), are similarly intermittent and of short duration.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Despite this perception, there are benefits of technology on ape welfare, for example, it can provide apes with a wide range of activities with varying levels of complexity, which allows it to be individually customizable and has the potential to be resistant to habituation on repeated exposure [5,[29][30][31]. Apes are able to engage directly and indirectly with technology [27,37,38] and therefore may provide a long-term solution to the need for cognitive stimulation [5], which would see an improvement in mental welfare. Additionally, through active participation, technology could benefit ape physical health [5].…”
Section: Technology and Ape Welfare 431 Natural Behavioursmentioning
confidence: 99%
“…Importantly, the MAB approach allows diverse behavioral engagement with a single relatively small apparatus-an aspect of interest for lowmaintenance enrichment devices. Another approach to diversity and flexibility in cognitive enrichment is a modular maze idea of the "Gorilla Game Lab" (Gray et al, 2018;Clark et al, 2019). Different problem-solving modules can be connected and flexibly arranged to create a changing enrichment device that is challenging in the long term.…”
Section: Introductionmentioning
confidence: 99%